АРХІТЕКТУРНІ ТА ТЕАТРАЛЬНІ КОДИ В ЛІТЕРАТУРНО-ХУДОЖНЬОМУ ТВОРІ - Коробкова, Наталія (Problems of Contemporary Literary Studies / Problemy Suchasnoho Literaturoznavstva, 2018)
The classic of the adventurous, detective, fantastic, and mysterious novel, Gaston Leroux got the enormous popularity through the cycle of eight detective novels united by the figure of a detective-amateur, professional reporter — Rultaby. It is believed that the author was his prototype. A well-known journalist, a lawyer, Gaston Leroux is the author of a large number various articles. But the real fame solidified through the musical based on his novel which was published in 1910. In 1986 English composer Baron Andrew Lloyd Webber created the most popular musical performance of the last quarter of the twentieth century — the musical «The Phantom of the Opera». In 2004 Joel Schumacher made the film based on the musical. These facts of culture became the object of the research. Today there are about thirty films based on Leroux works. The secret of such attention of cinema makers is in a specific artistic world of the product that provokes interdisciplinary intermedial transcoding, which is open to inter-artistic polylogue. The subject of this research is the intermedial cut of the novel. Intermedialism is viewed from two perspectives: as a phenomenon of art and as a method of analysis. Intermedial analysis is aimed at identifying the means of adjoining arts that are realized in the literature. Reading of painting, cinematographic or musical codes allows to reveal the semantic depths of the text, to find hidden values in the intricate discourses. The title of the novel focuses on the main character and place of action. The opera house is the main character. Leroux brings it to the metaphysical level, universalizing a very real architectural structure — Paris Grand Opera.The artist is interested in the antithesis of the top and bottom of the opera as two worlds: inspiration / creativity and hatred / fear, and consequently — good and evil. The similar principle is also used in the modeling of Phantom. His appearance sharply contrasts with his ingenious abilities. He is as ambivalent as the opera he serves. Compared with the novel, in the musical and the film, the main semantic focus is shifted to masks, which are active elements of action and get a symbolic meaning. They are a visual reflection of his inner world. In this way, his psychological portrait deepens, which allows to observe the evolution of the character. In the end, Eric refuses to wear a mask as a defense from the outside world and himself. Artistic and aesthetic concept of Gaston Leroux ’s novel «The Phantom of the Opera» acquires exclusive expression through intermedial accents. The main idea of the work is read through the architectural, theatrical, and musical contexts, which decoding contributes to the approach to the secret phenomenal talent of Leroux.